2021
DOI: 10.1021/acs.macromol.1c01038
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of β-Nucleating Agents Governing the Formation of the Crystalline Structure of Isotactic Polypropylene

Abstract: The effect of the morphological characteristics of N,N′-dicyclohexylterephthalamide (DCHT), an aromatic bisamide β-nucleating agent (β-NA) showing a dual nucleation capability for the β- and α-crystals of isotactic polypropylene (iPP), on the polymorphic composition of iPP and the underlying mechanism were systematically investigated. DCHT crystals differing in their size and distribution state in the iPP melt and recrystallized morphology were obtained by modulating the final heating temperature (T f), subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 67 publications
(111 reference statements)
1
28
0
Order By: Relevance
“…The polymorphic phenomenon is commonly found in semicrystalline polymers resulted from the different conformations and/or packing modes of molecular chains in the crystal cells [ 1 ]. The final crystalline modifications and crystalline structures depend on both the structure of molecular chains and the external crystallization conditions (e.g., the thermal conditions, the mechanical conditions, and the addition of nucleating agent, etc.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymorphic phenomenon is commonly found in semicrystalline polymers resulted from the different conformations and/or packing modes of molecular chains in the crystal cells [ 1 ]. The final crystalline modifications and crystalline structures depend on both the structure of molecular chains and the external crystallization conditions (e.g., the thermal conditions, the mechanical conditions, and the addition of nucleating agent, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the better toughness, improved heat resistance [ 1 ], high impact and tear strength [ 7 ] and improved elongation at break [ 8 ], β -iPP has attracted much attention in both academic and industrial research. Some researchers found that the Izod impact strength, flexural modulus and heat distortion temperature of an injection molded polypropylene increased with the β -crystal content within a certain range [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous nucleation, in general, is highly desirable because it controls the nucleation density during polymer processing. , As a result, nucleation reduces the average crystal size and size distribution and, in exceptional cases, allows to induce a specific crystal modification. Hence, heterogeneous nucleation can significantly alter the final property profile, including mechanical, electronic, and optical properties. , …”
Section: Introductionmentioning
confidence: 99%
“…24 Some agents were even synthesized specifically to further increase β-nucleating efficiency. [25][26][27][28] Nucleating agents with higher β-nucleation efficiency were reported constantly, such as calcium pimelate, 26,27 N,N′-dicyclohexylterephthalamide (DCHT), [28][29][30] WBG-II, 31 and TMB-5. 16 With these nucleating agents, the content of β-iPP can be increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of β-NA becomes a key issue affecting β-nucleating efficiency. It was found that with the increase of melting temperature, the morphology of β-NA changes constantly from granular, needle-like to dendritic, [28][29][30]32 leading to inhomogeneous dispersion of β-NA, which probably affects nucleation efficiency. Some researchers found that adding some undissolved agents such as TMB-5, 33 graphene oxide, 34 and ultrafine full-vulcanized powder rubber 35 can prevent the dissolved β-NA from selfassembling into large aggregates effectively.…”
Section: Introductionmentioning
confidence: 99%